Β-Arrestin-recruited phosphodiesterase-4 desensitizes the AKAP79/PKA-mediated switching of β2-adrenoceptor signalling to activation of ERK. (26th October 2005) - Houslay, M.D.; Baillie, G.S.
Abstract : Using combined dominant-negative and siRNA (small interfering RNA)-mediated knockdown strategies, the functional importance of specific PDE4 (phosphodiesterase-4) isoforms in modifying signalling through the β2 -AR (β2 -adrenoceptor) has been uncovered. The PDE4D5 isoform preferentially interacts with the signalling scaffold protein β-arrestin and is thereby recruited to the β2 -AR upon agonist challenge. Delivery of an active PDE to the site of cAMP synthesis at the plasma membrane specifically attenuates the activity of a pool of PKA (protein kinase A) that is tethered to the β2 -AR via AKAP79 (A-kinase anchoring protein 79). The specific functional role of this anchored PKA is to phosphorylate the β2 -AR and allow it to switch its coupling with Gi and thereby activation of ERK (extracellular-signal-regulated kinase). Our studies uncover a novel facet of the regulation of β2 -AR signalling by showing that β-arrestin-recruited PDE4 provides the means of desensitizing the agonist-dependent coupling of β2 -AR with Gi and its consequential activation of ERK.